Ischiofemoral impingement syndrome - Cuneyt Tamam (Arsiv Kaynak Tarama Dergisi, 2015)
Ischiofemoral impingement is newly recognized extracapsular cause of atypical hip and groin pain. Ischiofemoral impingement was first defined by Johnson in 1977. It is characterized by a narrowed space between the ischial tuberosity and the lesser trochanter, associated with changes in ischiofemoral space . The diagnosis of the ischiofemoral impingement is complex. Normal radiological and ultrasound appearances may be seen in ischiofemoral impingement patients with atypical hip pain. It is important to have a focus on the symptoms , through the history taking, physi and not;cal examination, and appropriate imaging studies of the hip.In this study, we aimed to review the etiology, clinical presentation, imaging modalities, differential diagnosis and treatment options of ischiofemoral impingement. [Archives Medical Review Journal 2015; 24(2.000): 271-281]